Intermedia Agenda-Setting Dynamics in Digital Media Reporting on AI Ethics - Ridwan Nasution; Febry Ichwan Butsi; Junedi Singarimbun; Nanang Arianto (Yayasan Darussalam Bengkulu, 2026)
The rapid expansion of artificial intelligence (AI) has generated growing ethical concerns related to governance, accountability, human rights, and social risk. In Indonesia, these concerns increasingly emerge within a complex media environment characterized by interactions between mainstream online news media and social media platforms. This study examines how AI ethics discourse is constructed and circulated through intermedia agenda-setting processes. The study uses a quantitative content analysis paired with intermedia agenda-setting approaches to examine AI ethical coverage in mainstream online news media and social media over a specific period. The findings show that mainstream online news media maintains agenda leadership in affecting the relevance and timeliness of AI ethical debate, notably through governance- and regulation-focused framing. However, social media plays an important complementary function by magnifying public concern and offering risk- and harm-oriented framing that might occasionally affect journalistic narratives. Frame transfer study reveals an unbalanced but interacting relationship in which institutional frames largely move from news media to social media, although experiential and moral frames may migrate in the reverse direction during periods of increased public attention. This study enhances intermedia agenda-setting theory by applying it to AI ethics and provides empirical insights into the media's influence on ethical communication and regulation of emerging technologies in Indonesia.